THE ROLE OF DA'I IN THE PROCESS OF DEVELOPING ISLAMIC EDUCATION ON KANGGE ISLAND: PERAN DA'I DALAM PROSES PENGEMBANGAN PENDIDIKAN ISLAM DI PULAU KANGGE - Dadi Nurjaman (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
The purpose of this study was to determine the role of preachers in the process of developing Islamic education in the coastal community of Kangge Island. Using qualitative research methods. The results of the study found that the first da'i was a facilitator. It is the da'i who have provided insight, motivated and discussed with the community, and then the results of the discussion were communicated to outside parties or stakeholders to get support in the development of Islamic education. Second, preachers as educators. That is, da'i are directly involved in becoming teachers. In addition, the da'i also held discussions with other teachers to formulate teaching and learning activities. The process of developing Islamic education through pdevelopment of community approach.